Jawabanmu

2014-05-31T20:09:16+07:00
L i m  √(3x-2) - x  = l i m (√(3x-2)-x)(√(3x-2)+x)
x⇒2   x²-7x+10       x⇒2 (x²-7x-10)(√(3x-2)+x)
                           =  l i m    (-x² + 3x - 2)
                               x⇒2  (x-2)(x-5)(√(3x-2)+x)
                           = l i m        (x - 2)(-x + 1)
                             x⇒3  (x-2)(x-5)(√(3x-2)+x)
                           = l i m             (- x + 1)          
                             x⇒2      (x-5((√(3x-2)+x)
                           =     - 2 + 1                
                                 (2-5)(√(6-2) + 2)
                           =         -1            
                                 -3(2+2)
                           = -1/-12 = 1/12